PERKUATAN DENGAN CERUCUK GALAM DI ATAS TANAH LUNAK - Zainal A Gaffar (Universitas Lambung Mangkurat, 2005)
Cerucuk galam is the answer for soil with soft clay condition which always soaked under water as effort of soil reinforcement. The use of cerucuk galam is very suitable with condition of alluvial soil that is widely spread inKalimantan, especially inSouth Kalimantan. There are many galam material inKalimantanand its prices relatively cheap. The use of many workers as galam wood seeker, distributor and driving pile cerucuk galam will reduce number of unemployment.This paper are based on observation and experience in the use of cerucuk galam to build up stockpile for PT. Tanjung Alam in Sungai Puting. There has not been teories yet that support the use of cerucuk galam as soil reinforcement. On this paper, the analysis is done with the use of theories approximation from Pusat Litbang Jalan, Badan Litbang P. U. based on experience in many soft clay soil location inIndonesia. The embankment on soft clay soil as coal truck traffic and as coal stockpile is not cause soil fall and the cost for build it is relatively low. Soil reinforcement with combination of cerucuk galam will bring good result on stabilization, safety and economic for build constructions on soft clay soil